Association of interarm blood pressure difference with selected body circumferences among Walter Sisulu University community - Wenzile S. Mthethwa; Nthai E. Ramoshaba; Zuqaqambe M. Mampofu (BMC, 2024)
Abstract Background A high interarm blood pressure difference (IAD) has been identified as a precursor of vascular diseases. Anthropometric measures for obesity such as body circumferences including waist circumference (WC), mid-upper arm circumference (MUAC) and neck circumference (NC) have been associated with a high IAD in Western countries. However, the prevalence of IAD and its association with body circumferences in South African communities such as universities is not well established. Therefore, this study aimed at investigating the correlation of IAD with selected body circumferences among the Walter Sisulu University (WSU) community. Methods A total of 230 participants, 117 males and 113 females, consisting of 185 students and 45 staff members from WSU, aged 18-27 and 18-63 years respectively, participated in this cross-sectional study. The selected body circumferences: WC, MUAC, and NC were measured using standard procedures. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured in both arms simultaneously using automated machines. IAD was achieved by calculating differences in SBP and DBP between the left (L) and right (R) arms, (R -L), and getting the absolute value, L-R (|L-R|). Results 14.78% of the participants had an interarm SBP difference (IASBPD) ≥ 10 mmHg, and 4.35% of participants had an interarm DBP difference (IADBPD) ≥ 10 mmHg. In a Pearson's correlation analysis, IASBPD was positively correlated with the selected body circumferences (WC, r = 0.29; P < 0.001; MUAC, r = 0.35; P < 0.001; NC, r = 0.27; P < 0.001) and mean arterial pressure (MAP) (r = 0.30; P < 0.001). In the multivariable-adjusted regression analyses, IASBPD was positively associated with MUAC (adjusted R 2 = 0.128, β = 0.271 (95% CI = 0.09; 0.60), P = 0.008), and NC (adjusted R 2 = 0.119, β = 0.190 (95% CI = 0.01; 0.32), P = 0.032) only, adjusted for MAP, age, gender, body mass index, smoking, and alcohol. There was no association of body circumferences with IADBPD. Conclusion A high IAD is common among students and staff members of the WSU community. Furthermore, IAD showed a positive correlation with MUAC and NC. These body circumferences can serve as indicators of high IAD, aiding in the early detection and prevention of vascular diseases.